(untitled) (Justicia &Derecho, 2020)
It is fundamental to identify the framework and measures taken to address the Global Financial Crisis and, therefore, prevent a future crisis. This is the primary purpose of the financial architecture. It is arguable that the financial architecture was proper to mitigate the consequences of the Global Financial Crisis. On the other hand, this architecture is not sufficient to address the challenges of the global finance. The main concern in the global finance is to avoid future crisis. The existing infrastructure will not avoid a future crisis. It is necessary to take steps for a proper regulation and policies considering resilience for banking sector and financial system in a macro landscape. Financial markets are not an end in themselves but mean: they are supposed to perform certain vital functions that enable the real economy to be more productive.